Política curricular de ação afirmativa: uma avaliação sobre o processo de implementação no Instituto Federal do Ceará - Freitas, Emerson de Melo (2020)
This research evaluates the implementation process of the National Curriculum Guidelines (DCNs) Ethnic-racial Relations Education (ERER) and for the afro-Brazilian and African Culture and History Teaching at the Federal Institute from Ceara (IFCE). As curriculum policy of affirmative action, such educational laws question the researcher-worker-evaluator to understand the evaluated object in the teacher training courses. This evaluation work has in its sustaining base the founding categories: education and ethnic-racial relations. Inspired by the Perspective of Evaluation in Depth, it comprehends the organization of methodological and epistemological presumptions to an evaluation counter-hegemonic of public policies. The analytical dimensions of context and content of this Exercise of Evaluation in Depth base the inductive exploration about the institutional path of the evaluative object. Therefore, the analytical dimensions of amplitude and density of the evaluative object point a evaluative path, comprising the IFCE as an empirical field and, the Fortaleza campus representing a section of this field. In this context, the instrumental procedures organize themselves in selection and analyses of institutional documents which show us how historically the evaluative object is representing the IFCE life path. As an intuitive strategy systematic observation is used, between December 2018 to December 2019, in the institutional processes which caused the starting adequacy of the Pedagogical Projects of Courses (PCCs) to the evaluative object in this period. Through analytical induction over the empirical field section an analysis of the degree PPCs in the face-to-face modality is used. To produce complementary data that enable analysis of the institutional representations over the evaluative object, it was conducted semi-structured interviews with subjects – implementers attached in the empirical field section, in the brief period between February 2020 to March 2020. Due the social isolation decrees because the Covid-19 pandemic, there was the necessity of a reduction in the interview numbers, then electronic means were used and the political quality of the interviewees. Finally, this Exercise of Evaluation in Depth uses the fundamental axes of the DCNs’ National Implementation Plan for ERER and for the afro-Brazilian and African Culture and History Teaching, in order to organize in qualitative evaluation indicators, the multidimensional analysis of the curriculum policy of affirmative action in the institutional trajectory of the Federal Institute from Ceara.